Development and validation of amino acid analysis methods in gelatin and gelatin-based products using high-performance liquid chromatography - Mohd Ismail, Azilawati (2016)
The similarity of physicochemical properties among gelatin especially the porcine and bovine gelatin has sparked skepticism among Muslim consumers towards gelatinbased commercial products. This study was aimed to develop and validate a reversephase high performance liquid chromatography (RP-HPLC) method of amino acid analysis in gelatin and differentiate the bovine, porcine and fish gelatin as an ingredient and in gelatin-based commercial products using the principal component analysis (PCA). The analytical method used was amino acid analysis that using 6- aminoquinolyl-N-hydroxysuccinimidyl carbamate as derivatization reagent and the chromatographic separation was determined by RP-HPLC coupled with a fluorescence detector. Method development was conducted according to ISO 17025 guidelines. In-house method validation revealed that the method was selectively performing a good chromatographic separation for 18 amino acids; the detection and quantitation limit were ranged from 5.68–12.62 and 36.0–39.0 pmol/μl, respectively; no matrix effect was observed and the linearity range was 37.5–1000 pmol/μl. Method precision revealed by HorRat values was significantly less than 2 and the method recoveries had a range of 80–115%. The uncertainty evaluation was estimated on the basis of the method validation data. The uncertainty of method precision, μ(P), method recovery, μ(R) and measurement of standard, μ(Std) for overall amino acids are within a concentration range of 0.024 to 0.113 pmol/μl, 0.006 to 0.10 pmol/μl and 0.010 to 0.0297 pmol/μl, respectively. PCA has assisted the process of distinguishing the bovine, porcine and fish gelatin. Data pre-treatments such as centering and area normalization were performed to reduce the variances of variables in dataset. Database for three gelatins were established through this work and were verified by samples from gelatin-based commercial products. Data analysis demonstrated that the fish gelatin was correlated to threonine, serine and methionine on the positive side of principal component (PC) 1; bovine gelatin was correlated to the non-polar side chains amino acids that were proline, hydroxyproline, leucine, isoleucine and valine on the negative side of PC1 and porcine gelatin was correlated to the polar side chains amino acids that were aspartate, glutamic acid, lysine and tyrosine on the negative side of PC2. The lowest detection value for adulteration of porcine gelatin in bovine gelatin was determined at 0.05% (w/w) of porcine gelatin. The extraction of gelatin from gelatin-based commercial products was successful by samples clean-up using acetone solvent and modification on several parameters of amino acid analysis method specifically the sample digestion process. Gelatin used in the commercial products was verified using gelatin database and the results revealed that products made of porcine gelatin can be differentiated from the products that were made of bovine gelatin. This quantitative method was very useful as an alternative method for halal products authentication via laboratory testing.